TOTAL HIP REPLACEMENT AND RELATED DIAGNOSIS RELATED GROUPS (DRG’s) IN THE GREEK HEALTHCARE SYSTEM - I. Tagarakis, Georgios; Dikeos, Costas; Tsilimingas, Nikolaos; Tsairidis, Charalampos; Tsolaki, Fani; Daskalopoulos, Marios; Polyzos, Nikolaos (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
Aim. To evaluate the Greek Diagnosis Related Groups(DRG’s)system in regard to the procedure of total hip arthroplasty. Methods. In a tertiary university orthopedics department implementing clinical protocols we recruited 75 consecutive patients planned to undergototal hip arthroplasty. Indicators of quality and performance were rates of mortality, pulmonary embolism, trauma dehiscence, disarticulation and readmission. Results. All rates of performance were excellent and equal to zero. The mean length of stay was almost identical to the one predicted by the Greek DRG’s. Conclusions. Clinical protocols are connected with good clinical results. The predicted by the Greek DRG’s hospital length of stay for total hip arthroplasty lies within pragmatic limits.